Drought Disaster Risk Assessment and Zoning in Gansu Province - Yang Ting; Cheng Yufei; Wang Junde (E3S Web of Conferences)
The special geographical location and complex climatic conditions of Gansu Province determine that the problem of drought disasters in Gansu Province will exist for a long time. Assessment and zoning of drought disaster risk is the basis for decision-making of drought risk management, the basic link of disaster prevention and mitigation, and the urgent need for sustainable economic and social development, which has important theoretical significance and application value. In this study, 87 county-level administrative regions in Gansu Province were taken as the evaluation unit, and the typical year method, percentile method, ArcGIS spatial analysis method were used to assess the risk of agricultural drought disaster, the risk of drinking water due to drought and the risk of urban drought disaster, and the drought disaster risk degree was calculated, and then the comprehensive risk of drought in Gansu Province were obtained, and the spatial distribution of drought risk in Gansu Province was analyzed. The research results can provide an important basis for formulating drought and disaster reduction programs, regional disaster prevention and mitigation strategies and plans, and regional economic and social sustainable development plans.